A GRASP ALGORITHM FOR GUILLOTINE CUTS - Ruiz Rivera, María (2006)
This work focus upon the first one, which, due to its high computational cost that causes us to obtain exact solutions, the use of a GRASP Algorithm for straight guillotine cuts, which allows to find good solutions for any instance in suitable times is thought to be used, having as the main goal to minimize the lost or waste of materials generated in the cutting process. This will allow us the enhancement of productivity and the reduction of costs making it attractive for applying it in the paper, glass, metal and wood industry sector.